Determination of Some Antineoplastic Agents in the Pure Form and in Their Pharmaceutical Preparation with N-Bromosuccinimide Reagent - I.C. SHUKLA; VINOD KUMAR; B.K. SINGH; O.P. YADAV; SANJAI KUMAR (International Journal of Pharma and Bio Sciences, 2010)
A simple, quick and convenient method has been developed for the determination of some antineoplastic drugs like cyclophosphamide, chlorambucil, melphalan, busulphan, methotrexate, mercaptopurine and 5-fluorouracil in pure form and in their pharmaceutical preparation with the use of Nbromosuccinimide reagent. The value of percentage error, coefficient of variation (CV) and standard deviation (SD) prove the method to be precise and reproducible. To establish authenticity of the method, recovery experiments were also carried out by standard drug addition method.